2017
DOI: 10.1002/hep.28990
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome in liver transplantation candidates with portopulmonary hypertension

Abstract: Stabilization or reversibility of PoPH seems to be an attainable goal using the combination of pulmonary arterial hypertension-targeted therapies and LT in patients who are transplantation candidates. (Hepatology 2017;65:1683-1692).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 32 publications
(60 reference statements)
3
61
0
1
Order By: Relevance
“…Included studies that reported survival data from a minimum of 20 patients. (14,(27)(28)(29)(30)32) *Unpublished data. Abbreviations: PH, pulmonary hypertension; N/A, not applicable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Included studies that reported survival data from a minimum of 20 patients. (14,(27)(28)(29)(30)32) *Unpublished data. Abbreviations: PH, pulmonary hypertension; N/A, not applicable.…”
Section: Discussionmentioning
confidence: 99%
“…(26,27) Post-LT resolution of POPH has been described, but clinical and hemodynamic worsening after LT has also been described. (28) Consequently, decisions regarding whether or not to pursue LT in patients with POPH, particularly in those without decompensated liver disease, are challenging. Recently, several studies have been published describing longterm outcomes of POPH following LT. (14,(27)(28)(29)(30) Although these experiences span a period of decades over which PAH therapeutic options have dramatically evolved, the cumulative reported experience in these studies has improved our understanding of both short-and long-term outcomes following LT. Posttransplant survival rates from these studies are summarized in Table 1.…”
Section: Myth: Little Is Known Regarding Long-term Posttransplant Outmentioning
confidence: 99%
See 1 more Smart Citation
“…Swanson et al reported superior 5‐year survival in patients receiving medical therapy before LT (67%) compared to patients who did not (25%). ( 1 ) Analysis of the other reports indicated that post‐LT outcome was numerically, although not statistically, better in studies including only patients who were pretreated ( 17,32 ) compared to studies reporting on a substantial ( 36 ) or intermediate ( 1,34 ) proportion of patients who were not medically pretreated. Pooled estimate rates of posttransplant deaths were 24% (95% CI, 15‐36) in pretreated patients versus 41% (95% CI, 21‐65) in patients who did not receive VM therapy (Q = 2.00; P = 0.16; Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Eleven studies were performed in Europe, ( 15,23,25,29‐36 ) 13 in the United States, ( 1,13,14,16‐18,20‐22,24,26‐28 ) one in Canada, ( 19 ) and one in Europe/United States/Brazil (the only RCT ( 37 ) ). Two studies reported on the outcome in untreated patients with PoPH.…”
Section: Resultsmentioning
confidence: 99%